Social Care and Gender: Who Cares for Dependent Adults in Spain? - de Vera, Violeta; Ondé, Daniel; Martín-González, Martín (Papeles de Europa, 2019)
Care work encompasses a series of tasks of distinct social and economic importance; however, it has not been a traditional object of study in Economics. The main objective of this article is to analyze the factors that intervene in informal care work in Spain. To approach this, an econometric analysis will be conducted using the National Health Survey (ENS as its Spanish acronym) carried out by the Instituto Nacional de Estadística (INE) of Spain. The results show that, in Spain, dependent adults do not receive the institutional support they need to perform basic daily activities. In fact, practically all of the care they receive is informal. This article will demonstrate that, within the household, women are responsible for informal care work whenever a family member is in need of such services. Our research shows that this is a consistent pattern regardless of the carer’s personal characteristics and level of education as well as the characteristics of the dependent adult living in the household. These findings reveal the necessity of reorienting public policies in order to help reduce gender inequalities caused by this socio-economic reality.